EReefs: An operational information system for managing the Great Barrier Reef. (20th November 2019) - Steven, Andrew D. L.; Baird, Mark E.; Brinkman, Richard; Car, Nicholas J.; Cox, Simon J.; Herzfeld, Mike; Hodge, Jonathan; Jones, Emlyn; King, Edward; Margvelashvili, Nugzar; Robillot, Cedric; Robson, Barbara; et al.
ABSTRACT: eReefs is a comprehensive interoperable information platform that has been developed for the Great Barrier Reef (GBR) region to provide users with access to improved environmental intelligence allowing them to assess past, present, and future conditions, as well as management options to mitigate the risks associated with multiple and sometimes competing uses of the GBR. eReefs is built upon an integrated system of data, catchment and marine models, visualisation, reporting and decision support tools that span the entire GBR area. This communication briefly describes eReefs architecture and components and provides examples of applications that have been used to inform policy and management decisions, and finally discusses challenges and key learnings and considers future developments and applications.